MECHANICAL AND CHEMICAL ACTIVATION OF BLAST FURNACE SLAG AND ITS INFLUENCE ON THE MECHANICAL PROPERTIES OF THE RESULTING CEMENT PASTE - Jan Horych; Pavel Tesárek; Zdeněk Prošek (Acta Polytechnica CTU Proceedings, 2021)
The usage of waste materials is a very important global topic. The large amount of waste everywhere in the world needs to be processed or disposed. Landfilling is not an option anymore, because of European legislation and restrictions. A lot of studies are trying to develop new options or possibilities of using waste materials. This research is trying to find a way to process blast furnace slag. A high-speed mill was used for the mechanical activation. Chemical activation was used as the next step of activation. There are many materials that could be used, but in this study we used slaked lime and water-glass. Slaked lime had a positive effect on mechanical properties. Samples had higher compressive strength but the effect was limited only for 5 wt. %. Another used material was water-glass, but in this case, there was a significant negative effect. Compressive strength and flexural strength were significantly reduced.